The Forming of Social Capital between Corporation and Community through the Implementation of CSR Programs: Case Study of An Offshore Oil and Gas Company in North Jakarta - Febrianti, Dwi Anisa (Masyarakat: Jurnal Sosiologi, 2018)
Corporate Social Responsibility (CSR) is a social obligation of companies established in Indonesia according to various applicable laws. However, CSR programs are applied differently between companies, depending on the company’s understanding of the CSR concept. Contrasting with previous studies which focused more on the evaluation of CSR programs and have not considered the relational impact of the CSR program implementation, this paper goes to observe the link between CSR programs and social capital. This article indicates that well implemented CSR programs establish social capital in the relations between the corporation and the local community. On the other hand, based on the stages of CSR program implementation, the company has not included the approach phase as one of the initial phases that should be executed by a company. This article also provides an overview that the implementation stages should not only stop at the evaluation stage, but should return to the initial stage of implementation, thus forming a cycle. This article was written based on a qualitative research to provide a better which was conducted in Pulau Kelapa, Kepulauan Seribu, North Jakarta, as the operational area of an offshore oil and gas company